Socio-pragmatic failure in English translations of euphemistic culture-bound expressions in the Qur'an by non-muslim translators - Shihan, Abd Ali Hammood (2016)
This study investigates socio-pragmatic failure in the translation of the culture-bound euphemistic expressions in the Qur'an since they imply many cultural aspects of Arabic. As used in the Qur'an, they have their own distinctive linguistic and nonlinguistic features, namely, they are highly euphemized, basically culture-dependent, and largely context-sensitive. Accordingly, the meanings and functions they tend to convey are not easily captured because they lie not in what is literally said but in what is intended. As a result, the selected translations of the said expressions seem to be replete with two major translation problems: (a) skewing and ambiguity of source text intentionality and (b) inaccuracy in rendering the pragmatic functions in the target text. Moreover, the studies on the Qur'an translation reviewed in this study had never examined the socio-pragmatic failure in the renditions of the culture-bound euphemistic expressions in the Qur'an. The importance of this study lies in identifying that such a failure perplexes the target reader's understanding of the original text and leads to cross-cultural communication breakdown. The following objectives are targeted in this study:(1) to investigate the Qur'anic intended meanings of the culturebound euphemistic expressions in the selected translations with reference to the Qur'anic exegeses,(2) to identify the extent to which the translators cited have retained the same pragmatic functions of source text in the target text, (3) to analyse the translation strategies translators of the Qur'an have adopted for translating the source text, and (4) to propose, as much as possible, the English functional-pragmatic equivalences to the culture-bound euphemistic expressions investigated. The data on the translation of source text were collected from the Qur'an and its four English translations carried out by four non-Muslim native speakers of English. The data, related to sexual matters and body effluvia, were selected for analysis on the basis that they are culture-bound and therefore difficult to translate. Qualitative content analysis was used to examine the source data by consulting the widely used traditional exegetical and rhetorical books to determine the source text intentionality. Additionally, the translated data were analysed according to the [exegetically-based] functional-pragmatic equivalence framework proposed by Searle (1969, 1975); Baker (1992, 2011); Gutt (1998, 2000). Further, the translated data were assessed according to House's (1997, 2001, 2015) model of translation quality assessment. The findings of the analysis revealed that the translators examined have followed three translation trends: Firstly, they are often “woodenly” literal to the extent of distorting the original or produce meanings not intended at all. Secondly, they have rendered the source text into English counterparts that imply negative connotations via dysphemizing the original that is highly euphemized. Thirdly, they try to render not only the textual but also the contextual meaning by resorting to exegetical interpretation. However, the present study concludes that the difficulty of accommodating the functional equivalence of the Qur'anic concepts in English can be overcome when the translator does his/her best in looking for the areas of common interest and experience in both the source culture and target culture.